Oxidation behaviour in Si-containing low-carbon steels. Issue 8 (24th May 2017) - Choi, Y. H.; Park, K.-S.; Jeong, T.-K.; Lee, J. S.; Suh, D.-W.
Abstract : Oxygen partial pressure at the boundary between external oxidation layer and steel matrix was determined by characterisation of internal oxidation in Si-containing low-carbon steels oxidised under atmospheric condition. The oxygen partial pressure calculated from the rate equation of the internal oxidation matches with the equilibrium value between Fe and FeO. From the oxygen partial pressure between external oxidation layer and steel matrix, the evolution of internal oxidation zone and the diffusion profile of solute Si were numerically simulated. The calculated depth of internal oxidation and solute Si profile accords to the measured ones from the EPMA, which implies that the numerical simulation captures reasonably the evolution of the internal oxidation in the Si-containing steels.